Penerapan Media Smart Box melalui Model Problem Based Learning pada Pembelajaran IPAS Kelas VI di SDN Sangen 02 Materi Sistem Saraf - Citra Prameswari; Dwi Nila Andriani; Rahayu Diningsih (Jurnal Pustaka Cendekia Pendidikan, 2025)
The low use of media in the science learning process is one of the reasons behind this research. The purpose of this study is to describe the application of Smart Box media for science learning in order to improve student learning outcomes in the nervous system material. The method chosen in this study is Classroom Action Research (CAR) by applying the Lewins model, namely planning, implementation, observation, and reflection. A total of 16 sixth grade students of SDN Sangen 02 became subjects in this study by conducting 2 cycles. Based on the findings of the researcher, the percentage of learning completion before and after applying Smart Box media in the pre-cycle was 58.25%, cycle I 75%, and cycle II 90%. Seeing the percentage of completion in cycle II of 90% has been met, so it can be concluded that the use of Smart Box media in learning can improve student learning outcomes and student enthusiasm during the learning process.